Modelos, estrategias, y recursos para la enseñanza mediada, en una asignatura de una carrera de grado - Belcastro, Ángela (2016)
This project displays aspects referred to the design of virtual learning environments (EVA) seen on the subject “Theoretical Informatics foundations”, from the third year and the second semester of an undergraduate degree of Argentina. The educational activities mediated by technology emerged from the development of research regarding the use of resources of the Web 2.0 in order to strengthen student´s learning abilities, and their professional skills. With the aim of promoting the significant development of learning skills, it is necessary to apply a right model of distance education, that supports the quality improvement of teaching learning processes, and helps to identify different subsystems involved and each of its elements, required in the design and the effective implementation of the educational proposal.